2009
DOI: 10.1021/ef8010959
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bio-Oil, Biogas, and Biochar from Pressurized Pyrolysis of Wheat Straw Using a Tubular Reactor

Abstract: The main objective of this work was to examine the influence of pyrolysis pressure on product yield from wheat straw pyrolysis. The experiments were performed in a tubular reactor at different pressures (10, 20, 30, and 40 psi) with a constant flow rate of nitrogen (50 cc/min) at a temperature of 500 °C. During pyrolysis, the products obtained are oil, gas, and char. The maximum oil yield was 37.6%, obtained at high pressure (40 psi). Liquid product was analyzed using gas chromatography/mass spectrometry (GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(100 citation statements)
references
References 23 publications
5
90
3
2
Order By: Relevance
“…Furfural, D-allose and phenolic compounds are the main chemical compounds in the bio-oil for the three kinds of biomass. Similar results were reported in our previous research [23,32] and the work of Mahinpey [5]. Properties and chemical composition of bio-oil are distinct from petroleum fuel because of its relatively high content of water and solids, acidity and instability when heated [26].…”
Section: Gc-ms Analysis Of Bio-oilsupporting
confidence: 89%
See 2 more Smart Citations
“…Furfural, D-allose and phenolic compounds are the main chemical compounds in the bio-oil for the three kinds of biomass. Similar results were reported in our previous research [23,32] and the work of Mahinpey [5]. Properties and chemical composition of bio-oil are distinct from petroleum fuel because of its relatively high content of water and solids, acidity and instability when heated [26].…”
Section: Gc-ms Analysis Of Bio-oilsupporting
confidence: 89%
“…It can be seen in Tables 3-5 that 30, 25 and 22 kinds of chemical compounds were detected from white ash, switchgrass and corn stover bio-oils, respectively. It has been reported that bio-oils produced from different types of biomass samples under similar conditions have similar composition [5]. Table 3 shows that the white ash bio-oils (300°°C, 400°°C and 500°°C) had a large amount of compounds including furfural (relative mol contents were 10.15%, 14.97%, 12.35%, respectively), Butyrolactone (relative mol contents were 8.15%, 8.10%, 6.58%, respectively), metacetamol (relative mol contents were 8.36%, 11.70%, 8.11%, respectively) and D-allose (relative mol contents were 5.68%, 11.46%, 10.19%, respectively).…”
Section: Gc-ms Analysis Of Bio-oilmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to traditional pyrolysis procedures for biochar generation, alternate methods have been discovered. Comprises: 1) pressurized pyrolysis [82]; 2) hydrothermal carbonization [83] [84] [85]; 3) microwave pyrolysis [86]. These latter procedures have potential as ways to resources with properties external the range of usual pyrolysis products and greater energy efficiency.…”
Section: Physico-chemical Characterisation Of Biocharmentioning
confidence: 99%
“…Most of the compounds identified through in the bio-oils originated due to the thermal cracking of cellulose, hemicellulose and lignin in the biomass. Numerous amounts of compounds were identified in the bio-oils (Mahinpey, Murugan, Mani, & Raina, 2009). Due to their diversity, they were categorized into five major classes, namely monoaromatics, polyaromatics, aliphatics, oxygenates and nitrogenates.…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 99%